Development of generic first-order release paracetamol tablets - Selma Pedersen Kjartansdóttir 2001-; Úrsúla Hanna K. Karlsdóttir 1996-; Hanna Margrét Jónsdóttir 1999- (2023)
Paracetamol, also known under the name acetaminophen is a very known substance in Iceland as well as across the world. Paracetamol can be found in various dosage forms including tablets, suppositories, syrups, and capsules. It is a non-prescription analgesic and is used for mild to moderate fever and pain. The aim of this project was to develop and formulate paracetamol tablets with a first- order release profile with a dissolution profile within 5% error to the reference drug, Dolorin®, from the pharmaceutical company Williams & Halls. This percentage is set by the European Medicines Agency to ensure bioequivalence to the reference drug. There were ten different formulations produced, all of them contained similar excipients as Dolorin but changed slightly until the formulation with the most similar dissolution profile as Dolorin was found. The final formulation, formulation 10, showed the most similarities to the reference drug and was therefore used to undergo the tests that the European Pharmacopeia sets for quality control. This formulation contained, like Dolorin, 500 mg of the active ingredient paracetamol, as well as the excipients such as pregelatinized maize starch, povidone, microcrystalline cellulose and magnesium stearate. This final formulation passed all but two European Pharmacopeia tests, the disintegration test and the uniformity of content test.